Comparison of methods to detect resistance of Helminthosporium solani to a thiabendazole fungicide - Saunders, J.M.; Errampalli, D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2001)
The development of resistance to a post-harvest and preplanting benzimidazole fungicide, thiabendazole (TBZ), has resulted in the increase of silver scurf of potato caused by Helminthosporium solani. Conventional and polymerase chain reaction (PCR)-based assays were compared, among 54 isolates of H. solani, to detect the TBZ-sensitive (TBZS) and -resistant (TBZR) isolates. In a PCR-based assay, all 27 single-spore isolates from eastern Canada, nine isolates from Alberta in western Canada, six isolates from North Dakota, USA were distinguished as TBZR, the remainder of the isolates being determined as TBZS. The results from the PCR-based assay correlated well with the TBZ sensitivity assessment of isolates of H. solani on the TBZ-amended medium. Also, the detection of TBZR- H. solani in 20 tuber samples with silver scurf lesions by the PCR-based assay demonstrates that this method can be used to detect the pathogen directly from the tuber lesions. The PCR-based method was more rapid (1 day) than the conventional technique (5 weeks).